Experimental evaluation of system characteristics «compressor stage–linear magnetoelectric drive» - A. A. Tatevosyan; S. S. Busarov; A. V. Nedovenchany; I. S. Busarov; A. O. Zhukov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this work, tests of low-speed compressor stages with a linear magnetoelectric drive are carried out. The developed system makes it possible to measure the instantaneous parameters of the compressed gas in the working chamber of the piston stage, as well as to take the operating characteristics of the drive — consumed current, voltage, power. The work presents examples of the obtained characteristics. In the future, the use of the measuring system is assumed in scientific research on the study of effective modes of operation of the magnetoelectric drive and as a teaching and laboratory stand in the implementation of the educational process